2008
DOI: 10.1590/s1809-29502008000200002
|View full text |Cite
|
Sign up to set email alerts
|

Comparação dos efeitos da estimulação elétrica nervosa transcutânea e da hidroterapia na dor, flexibilidade e qualidade de vida de pacientes com fibromialgia

Abstract: Este estudo visou comparar a eficácia da hidroterapia e da estimulação elétrica transcutânea do nervo (TENS) na melhora da sintomatologia de pacientes com fibromialgia Participaram do estudo 10 sujeitos com fibromialgia (48,8±9,8 anos) divididos em dois grupos: um tratado com hidroterapia e outro com TENS. Todos foram avaliados antes e após o tratamento quanto à flexibilidade (pelo índice terceiro dedo-solo), dor (por escala visual-analógica), qualidade de vida relacionada à saúde (pelos questionários SF-36 e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0
22

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(48 citation statements)
references
References 24 publications
(20 reference statements)
0
26
0
22
Order By: Relevance
“…The content analysis of selected clinical trials revealed the use of laser modalities [17][18][19][20] , interferential current (IFC) alone 21 , IFC combined with ultrasound 22 and transcutaneous electrical stimulation (TENS) 23 as therapeutic modalities proposed for FMS treatment. No studies on thermal modalities were found.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The content analysis of selected clinical trials revealed the use of laser modalities [17][18][19][20] , interferential current (IFC) alone 21 , IFC combined with ultrasound 22 and transcutaneous electrical stimulation (TENS) 23 as therapeutic modalities proposed for FMS treatment. No studies on thermal modalities were found.…”
Section: Resultsmentioning
confidence: 99%
“…To determine the clinical diagnosis of FMS that was necessary for participant inclusion, most studies [17][18][19][20][21][22][23] (n=6) applied the criteria proposed by the American College of Rheumatology (ACR). The samples consisted exclusively of female participants, with exception to the study by Gür et al 18 that contained 15 male participants who were exposed to laser therapy (n=5) or control (n=10).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations